Factors influencing germination of a functionally important grassland plant, Iris tenax. - Katherine D Jones; Thomas N Kaye (PLoS ONE)
Grassland prairies of western Oregon and Washington are among the most endangered ecosystems in the United States. Active management and restoration are needed to promote biodiversity in the region. To support plant production for use in habitat restoration, we developed germination protocols for greenhouse propagation of Iris tenax (Oregon iris). Dormancy was most effectively overcome (63% germination) by four weeks of warm stratification at 20/30°C followed by 6-12 weeks of cold stratification at 5°C suggesting that I. tenax may have morphophysiological dormancy. This result was consistent across multiple source populations.